Effects of V substitution and annealing on Zr-based AB2 alloys as anode material of metal hydride batteries. (December 2020) - Wan, ChuBin; Jiang, XiaoPing; Qi, Ying; Ju, Xin
Abstract: Present paper investigates Ti0.25 Zr0.75 Ni1.35-x Mn0.65 Vx (x = 0, 0.05, 0.1, and 0.15) alloys as anode active materials of metal hydride batteries. The AB2 Laves-type alloys are prepared using arc melting and annealing. The as-cast alloys contain the major C15 and/or C14 intermetallic compounds together with the Ti–Ni and Zr–Ni secondary phases. The annealing promotes the homogeneity of the alloys and dismisses the non-Laves phases. As the V contents increase, the C15-type Laves phase transforms to the C14 structure. In addition, the unit cells of the Laves phase increase as the V contents in the alloys increase. All the studied alloy electrodes reach their maximum discharge capacities during the first 10 activation cycles. After charge/discharge 100 cycles at 300 mAg −1, the discharge capacity retentions of all the studied alloy electrodes keep more than 75%. Annealing treatment and V substitution increase the full discharge capacity from ~230 mAg −1 for N1 alloy to ~430 mAhg −1 for A4 alloy. The synthetic effects between V substitution and annealing are studied on improving the phase structure and the electrochemical properties of AB2 -type Laves phase alloys. Graphical abstract: Image 1 Highlights: No high-cost metals were used in the studied alloys to decrease the alloy cost. The V substitution leads to the transformation from C15 to C14 structure. Annealing treatment increases the abundances of Laves phases. A higher discharge capacity, 433 mA h/g of the annealed alloy with a higher V level. V substitution and annealing play positive effects on electrochemical properties.